Price Fairness, Consumer Attitude, and Loyalty in the U.S. Egg Market: The Moderating Roles of Tariff Concern and Education Level - Min Gyung Kim; Joonho Moon (Foods, 2025)
The primary objective of this study is to investigate the relationships among perceived price fairness, consumer attitude, and loyalty in the context of egg consumption. In addition, the study examines the moderating effects of tariff-related concern and education level on these relationships. Data were collected through an online survey administered via the Clickworker platform, resulting in a sample of 311 U.S. consumers. The proposed hypotheses were tested using Hayes’s Process Macro (Model 7). The results reveal that both perceived price fairness and consumer attitude have significant positive effects on loyalty toward eggs. Moreover, a strong positive association was found between consumer attitude and loyalty. The analysis also identifies the moderating roles of tariff concern and education level, particularly in the relationship between price fairness and loyalty. This research contributes to the existing literature by offering insights into the dynamic interplay of five key variables in the context of consumer behavior within the egg market. Also, this research proposes practical implications focusing on various stakeholders.